PERUBAHAN TEKANAN DARAH PADA LANSIA HIPERTENSI MENGGUNAKAN ALAT PIJAT REFLEKSI KAKI ELEKTRIK DI PSTW JEMBER - Muhammad Amin; Sujud Priyono (Jurnal Kesehatan dr. Soebandi, 2018)
The process of aging in humans occurs changes throughout the system in the body one of which cardiovascular system whose manifestations are hypertension. Hypetension is a chronic condition in which blood pressure in artery walls (clean blood vessels) increases. Treatment of hypertension can be done by non-pharmacological means of electric massage therapy. This study aims to determine changes in blood pressure in hypertensive elderly based on an electric foot reflexology massage tool at Tresna Werdha Jember Social Home. The design of this study was quasy one group pretest posttest experiment. Population 32 elderly with samples using total sampling technique. The instrument used in this study was an electric massage tool using an observation checklist, while to measure blood pressure, researchers used a sphygmomanometer. Paired t-test statistical test with a significance level a <0.05, the results of the study showed a reduced systolic and diastolic mean. There is a change in blood pressure before and after an electric massage is given for a better decrease in pressure changes. For nursing staff this method can be used as a treatment for high blood pressure with more precise supervision